Penentuan Nisbah Bagi Hasil Pada Pembiayaan Mudharabah Dan Perlakuan Akuntansinya (Studi Kasus Pada KSPPS BMT NU Cabang - Imamah, Iin Fadilatul (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.08.NO.02.TAHUN 2019, 2019)
This study aims to determine the determination of profit sharing ratio and to analyze the accounting treatment on mudharabah financing products. Shariah financial institutions that are used as objects in this study is a Savings and Loans Cooperative and Sharia (KSPPS) BMT NU Branch Wringin Bondowoso. This research is conducted by direct interview with head of branch or head of BMT NU Wringin Branch and describe all data of determination of profit sharing ratio in mudharabah financing which then analyze the suitability of mudharabah financing accounting in BMT NU with PSAK no. 105. Based on the research that has been done, it can be concluded that the determination of profit sharing ratio in the mudharabah financing product using the method of calculating the average gross income and treating the accounting on the recognition, measurement, presentation and disclosure on mudharabah financing still exist that is not in accordance with the PSAK. 105.